Effectiveness of Law Enforcement for Traffic Violators via Mobile ETLE in the Pasuruan Police Legal Area (Advances in Police Science Research Journal, 2024)
The number of traffic violations in Pasuruan Regency is fluctuating and decreasing drastic changes in 2023 raises questions regarding enforcement management traffic violation laws in that jurisdiction. This research aims to describe the effectiveness of the ETLE Mobile program in law enforcement traffic violators and the implementation of law enforcement against traffic violators via ETLE Mobile in the jurisdiction of the Pasuruan Police. This research uses qualitative descriptive method. Data collection techniques use observation techniques, interviews and document review. The data analysis techniques use techniques data reduction, data presentation and drawing conclusions. Results of this research shows that the effectiveness of law enforcement for traffic violators through ETLE Mobile is said to be ineffective because the budget is still insufficient, problems with infrastructure that still have obstacles and lack of them personnel at Urtilang. Then for management of law enforcement implementation traffic violators via ETLE Mobile based on POAC analysis results, on Personnel planning, budget and infrastructure are still not optimal. Meanwhile, the organization, implementation and supervision have been completed run optimally.
Keywords: Kata Kunci: Efektivitas, ETLE Mobile, Pelanggaran Lalu Lintas, Penegakan Hukum.